(Re)viewing organizational reputation in a global context / Sanjiv S. Dugal, Matthew H. Roy and Matthew Eriksen - S. Dugal, Sanjiv; H. Roy, Matthew; Eriksen, Matthew (Faculty of Business and Management ; UiTM Press, 2002)
An organization undertaking competitive actions possesses different "reputations" that vary in terms of their perception among stakeholders. This paper is about perception, that is, how do viewers come to perceive an organization in a certain way. We review the processes of reputation and identity. Further, we explain perceptual space and its' implications for reputation formation. Lastly we provide some food for thought for recreating reputations in today's chaotic globalized business world.